Business strategy for Viet trading Technology Investment Development Joint – Stock company 2019-2025 - Mai, Van Chinh (Khoa Quốc tế, ĐHQGHN, 2020)
VNTECH is a firm which is now doing business in installation and construction industry. The purposes of this study are to study basis for building strategies, process of building strategies and methods of analyzing and selecting the best strategies aiming to help VNTECH choosing the most suitable strategies, to identify and to apply business strategy theories to build the best business strategy for VNTECH for the period 2019-2025, and to provide recommendations solutions in order to implement and successfully perform the business strategy so that VNTECH becomes a powerful player both in the Vietnamese and in the world market.